2020
DOI: 10.1210/jendso/bvaa173
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in Gut Microbiota Do Not Play a Causal Role in Diet-independent Weight Gain Caused by Ovariectomy

Abstract: Acute estrogen deficiency in women can occur due to many conditions including hyperprolactinemia, chemotherapy, GnRH agonist treatment, and removal of hormone replacement therapy. Ovariectomized (OVX) rodent models, often combined with a high-fat diet (HFD), have been used to investigate the effects of decreased estrogen production on metabolism. Since evidence suggests that gut microbes may facilitate the protective effect of estrogen on metabolic dysregulation in an OVX+HFD model, we investigated whether the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 60 publications
(59 reference statements)
1
8
0
Order By: Relevance
“…Ten taxa were increased during STND compared to HFD, including Turibacteriales (class), its family Turibacteriaceae and the genus Turibacter, as reported previously [49]. The relative abundances of the family Clostridiaceae and its genus Clostridium and Coprococcus were also increased during STND compared to HFD.…”
Section: Estradiol Alters Relative Abundances Of Gut Microbiota In Female Micesupporting
confidence: 83%
See 1 more Smart Citation
“…Ten taxa were increased during STND compared to HFD, including Turibacteriales (class), its family Turibacteriaceae and the genus Turibacter, as reported previously [49]. The relative abundances of the family Clostridiaceae and its genus Clostridium and Coprococcus were also increased during STND compared to HFD.…”
Section: Estradiol Alters Relative Abundances Of Gut Microbiota In Female Micesupporting
confidence: 83%
“…Similarly, in a PCOS mouse model, FMT from androgen-treated mice disrupts metabolic and endocrine health in germ-free recipients, whereas gut microbiota from control donors protects against metabolic dysregulation [ 60 , 61 , 62 ]. In a different study, diet-independent, ovariectomy-induced weight gain was not rescued by cohousing with intact mice, with the goal of transferring of gut microbiota [ 49 ]. It is possible that a more complete transfer of microbiota is needed to rescue this ovariectomy-induced weight gain, such as fecal microbiota transfer (FMT) by gavage or co-housing combined with FMT.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that gut microbiota elicits a variety of responses based on the factors contributing to metabolic disorders. For example, a transfer of healthy microbiota attenuated body weight gain and improved insulin response in PCOS models of female mice) ( 60 ), whereas did not prevent ovariectomy-dependent obesity ( 67 ). Most importantly, the present findings provide a compelling justification for further investigation of sex differences in basic and clinical studies in the function of gut microbiota in metabolic health.…”
Section: Discussionmentioning
confidence: 99%
“…Soy isoflavones, which exhibit estrogen-like properties, can significantly change the fecal bacterial community in postmenopausal women [99]. In ovariectomized mice, ovariectomy was associated with a shift in the beta diversity of the gut microbiota analyzed by 16S rRNA gene sequence analysis [100]. A recent study showed that Verrucomicrobia and Actinobacteria were significantly increased in ovariectomized mice compared with a control group [101].…”
Section: Immunomodulatory Effects Of Estrogenmentioning
confidence: 99%